EVALUASI PROSPEKTIF KADAR NEUTROPHIL GELATINASE- ASSOCIATED LIPOCALIN URIN DAN KREATININ SERUM PASIEN ACUTE KIDNEY INJURY PASKA PEMBEDAHAN - Arya Nugrah, Putu; Sudhana, I Wayan (journal of internal medicine, 2014)
Acute Kidney Injury (AKI) is a common clinical nding that produces some serious health problem. Since the previously decades, the identication of AKI clinical practically based on laboratory test as Blood Urea Nitrogen (BUN) and Serum Creatinin (SC). Unfortunatelly, SC is not a reliable indicator of AKI in acute phase. Neutrophil Gelatinase-Associated Lipocalin (NGAL) is promisingly for an early biomarker of ischemic kidney injury. After performing the inclusion criteria and exclusion criteria, samples are underwent the operation then admitted to the ICU ward. Samples were followed and underwent serially laboratory examination of urine NGAL, SC and urine output according to the timetable of the research. Mean concentration of SC before operation and hour 0 hour, 6 hours, and 24 hours after operation for non AKI patients were as follow 0.83 ± 0.19 mg/dl; 0.83 ± 0.19 mg/dl; 0.89 ± 0.18 mg/dl; and 0.88 ± 0.25 mg/dl. And for AKI patients were 0.86 ± 0.21; 0.81 ± 0.20 mg/dl; 1.01 ± 0.20 mg/dl; and 1.84 ± 0.75 mg/dl. Mean concentration of urine NGAL on 0 hour, 3 hours, and 6 hours post operation non AKI patients were as follows 26.0 ± 27.7 ng/l; 24.4 ± 23.0 ng/l; and 32.6 ± 42.4 ng/l. While in AKI patients were 809.4 ± 379.0 ng/l; 732.0 ± 450.0 ng/l; and 651.4 ± 432.0 ng/l. The elevated concentration of urine NGAL among cases of AKI occurred earlier than the elevated concentration of SC.
Keywords: Urine NGAL, biomarker, AKI